High-Speed Photodiodes in Standard CMOS Technology - Radovanovic, Sasa; Annema, Anne-Johan; Nauta, Bram (The Springer International Series in Engineering and Computer Science ;, 2006)
High-speed Photodiodes in Standard CMOS Technology describes high-speed photodiodes in standard CMOS technology which allow monolithic integration of optical receivers for short-haul communication. For short haul communication the cost aspect is important , and therefore it is desirable that the optical receiver can be integrated in the same CMOS technology as the rest of the system. If this is possible then ultimately a singe-chip system including optical inputs becomes feasible, eliminating EMC and crosstalk problems, while data rate can be extremely high. The problem of photodiodes in standard CMOS technology it that they have very limited bandwidth, allowing data rates up to only 50Mbit per second. High-speed Photodiodes in Standard CMOS Technology first analyzes the photodiode behaviour and compares existing solutions to enhance the speed. After this, the book introduces a new and robust electronic equalizer technique that makes data rates of 3Gb/s possible, without changing the manufacturing technology. The application of this technique can be found in short haul fibre communication, optical printed circuit boards, but also photodiodes for laser disks.